Tuning of Thermoelectric Property in the Flexible MWCNT Buckypaper - Liu1, Jih-Hsin; Miao1, Hsin-Yuan; Saravanan3, L.; Wang2, Li-Chih; Tsai1, Ren-Hui (Asian Journal of Chemistry, 2013)
In this work, we report the preparation of flexible carbon nanotube buckypaper for thermoelectric applications. Different thermoelectric semimetal deposited multiwalled carbon nanotube buckypaper was prepared by the thermal evaporation method. Low temperature resistivity measurement was performed to confirm the semi-conducting nature of the synthesized carbon nanotube networks. We also demonstrated the significant increase in the S(T) value by connecting 3 layers of buckypaper in series. We studied here on increasing the Seebeck coefficient and the electrical conductivity to enhance the thermoelectric power factor (S2s) thereby improving the thermoelectric efficiency of the multiwalled carbon nanotube buckypaper.